P649 Uncommon complication after congenital diaphragmatic hernia repair in a newborn. (June 2019) - Charfi, Manel; Hamad, Amel Ben; Zitouni, Hayet; Regaieg, Chiraz; Bouraoui, Amira; Regaieg, Ridha; Hmida, Nedia; Mhiri, Riadh; Thabet, Afef Ben; Gargouri, Abdellatif
Abstract : Introduction: Bowel intussusception is an extremely rare postoperative complication of congenital diaphragmatic hernia. Any delayed diagnosis can be life-threatening. Clinician has to evoke the diagnosis every time symptoms of bowel obstruction appear after surgical repair. Methods: We report the case of a newborn who presented an acute intussusception at the fourth post operative day of a congenital diaphragmatic hernia repair. Results: A female full term newborn was operated for a congenital diaphragmatic hernia at her second day of life. Four days after surgery she started vomiting bile-stained fluid. Abdominal ultrasound showed an ileoileal intussusception with the classic target sign. Laparotomy evidenced a jejunojejunal intussusception associated to multiple intestinal adherences. The intussusception was manually reduced and the intestinal adhesions were released. The postoperative course was uneventful. She is now 2 years-old and she is healthy. Conclusions: In our case, intestinal intussusception would be secondary to postoperative intestinal adhesions and peristalsis disorders during the phase of its reactivation in the first postoperative days.